Ante Mortem Molecular Diagnosis of Rabies from Saliva and Skin - Singh, CK; Bansal, K; Dandale, M; sharma, Pranoti (Asian Journal of Biological and Life Sciences, 2012)
With the advent of molecular approaches, antemortem diagnosis of rabies has become more productive and meaningful. For antemortem diagnosis of rabies two most significant samples that have been projected by various workers are saliva and skin. The present review gathers the research studies carried out on saliva and skin by employing various molecular approaches. Molecular approaches reported by various workers for diagnosis of rabies virus are compared.